AlGaAs/GaAs solar cell with CNT transport layer: numerical simulation. (December 2019) - Raudik, S A; Mozharov, A M; Mitin, D M; Bolshakov, A D; Fedorov, V V; Neplokh, V V; Rajanna, P M; Nasibulin, A G; Mukhin, I S
Abstract: AlGaAs/GaAs solar cells (SC) was modeled. Conventional SC was compared with structure with the thinner emitter. SC with additional CNT transport layer was simulated and compared with SC without it. The simulation was carried out with different geometry of the contacts and light flux. CNT transport layer has allowed achieving an increase in SCs efficiency up to 1.7% compared with metal contact grid.